Provable Security 7th International Conference, ProvSec 2013, Melaka, Malaysia, October 23-25, 2013. Proceedings - Susilo, Willy; Reyhanitabar, Reza.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 7th International Conference on Provable Security, ProvSec 2013, held in Melaka, Malaysia, in October 2013. The 18 full papers presented together with 1 invited talk were carefully reviewed and selected from 44 submissions. The papers cover the following topics: key exchange protocols, security models, signature and signcryption schemes, authenticated encryption, theory, and public key encryption.
On Modeling Terrorist Frauds: Addressing Collusion in Distance Bounding Protocols -- Authenticated Key Exchange Protocols Based on Factoring Assumption -- Efficient, Pairing-Free, Authenticated Identity Based Key Agreement in a Single Round -- CIL Security Proof for a Password-Based Key Exchange -- Non Observability in the Random Oracle Model -- Indistinguishability against Chosen Ciphertext Verification Attack Revisited: The Complete Picture -- Input-Aware Equivocable Commitments and UC-secure Commitments with Atomic Exchanges -- Towards Anonymous Ciphertext Indistinguishability with Identity Leakage -- k-Time Proxy Signature: Formal Definition and Efficient Construction -- Anonymous Signcryption against Linear Related-Key Attacks -- Improved Authenticity Bound of EAX, and Refinements -- The Security of the OCB Mode of Operation without the SPRP Assumption -- A Short Universal Hash Function from Bit Rotation, and Applications to Blockcipher Modes -- How to Remove the Exponent GCD in HK09 -- Translation-Randomizable Distributions via Random Walks -- RKA Secure PKE Based on the DDH and HR Assumptions -- Computationally Efficient Dual-Policy Attribute Based Encryption with Short Ciphertext -- Factoring-Based Proxy Re-Encryption Schemes -- Towards a Secure Certificateless Proxy Re-Encryption Scheme.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Information systems; Computer Science; Data Encryption; Systems and Data Security; Computers and Society; e-Commerce/e-business.; Computer Appl. in Administrative Data Processing; Computer Science, general